2011
DOI: 10.1016/j.epidem.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling management strategies for a disease including undetected sub-clinical infection: Bacterial kidney disease in Scottish salmon and trout farms

Abstract: Disease is a major constraint on animal production and welfare in agriculture and aquaculture. Movement of animals between farms is one of the most significant routes of disease transmission and is particularly hard to control for pathogens with subclinical infection. Renibacterium salmoninarum causes bacterial kidney disease (BKD) in salmonid fish, but infection is often sub-clinical and may go undetected with major potential implications for disease control programmes. A Susceptible-Infected model of R. salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…A fourth category has been used previously by differentiating the subclinical category into ‘unknown infected’ and ‘known infected’ (Murray et al . ) Although test positives may have been classified as known cases and field observations as unknown cases to further subdivide our case definitions, simplicity and reflecting industry practice did not warrant expanding beyond three categories.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth category has been used previously by differentiating the subclinical category into ‘unknown infected’ and ‘known infected’ (Murray et al . ) Although test positives may have been classified as known cases and field observations as unknown cases to further subdivide our case definitions, simplicity and reflecting industry practice did not warrant expanding beyond three categories.…”
Section: Discussionmentioning
confidence: 99%
“…Using a model tailored towards sea lice management, Murray and Salama (2016) showed that synchronization of management measures such as medication and fallowing within the same management areas is key to highly effective protection. Murray et al (2011) describe how for infections with bacterial kidney disease caused by Renibacterium salmoninarum, management could be more effective. Towards this end, these authors concluded that not only farms with clinically diseased animals, which are already put under oversight and shut off (no fish movement), but also measures should be taken on other farms with potentially sub-clinically infected salmon, as well as improved surveillance .…”
Section: Disease Transmissionmentioning
confidence: 99%
“…These results are in agreement with previous reports indicating that both the number (Bruno ) and proportion (Bruno ; Munro ; Murray et al . , ) of R. salmoninarum ‐infected rainbow trout sites are greater than for Atlantic salmon sites. The statistics assume, however, that the biennial site testing is completely reliable with perfect diagnostic sensitivity (Se) and specificity (Sp).…”
mentioning
confidence: 90%
“…Summaries of the number of reported wild fish with BKD in Scotland (Smith ; Bruno ) or, following the widespread adoption of aquaculture, the number and/or proportions of production sites (hereafter referred to as sites) infected with R. salmoninarum have been provided (Bruno , ; Munro ; Murray et al . ; Murray et al . ) although uncertainty regarding the prevalence remains among fish health professionals (Murray & Soje ).…”
mentioning
confidence: 99%